The Effect of a Workshop Change on Skills Writing Scientific Articles and Information Literations - Lenni Marlina; Saefudin; Kusnadi (ICHELSS: International Conference on Humanities, Education, Law, and Social Sciences, 2021)
Abstract: 21st century craftsmanship is an era full of competition and global environmental issues. Students must be equipped with information literacy and writing skills to be able to face 21st century competition. The general objective of this research is to determine the skills of writing popular scientific articles and information literacy of students through online workshops. This research is a descriptive study, with a weak experiment method, the number of respondents was 30 high school class X students. To determine the increase in students’ ability to write scientific articles before and after the workshop was held pretest and posttest by giving portfolio assignments. Based on the results of the research, online workshops on writing scientific articles had an influence on the writing of scientific articles of students seen from the average pretest results of 5.4 while the average posttest results were 8.3. This shows a significant difference in the writing of students’ scientific articles. Students’ understanding of information literacy is in good category. This is indicated by the average percentage of the achievement indicators of 73,3%. Thus, online workshops can be used as a means for teachers to improve scientific article writing skills and student information literacy. Keywords: Workshop, Writing Skills, Information Literacy.